The Metabolic Reprogramming of Frem2 Mutant Mice Embryos in Cryptophthalmos Development - Zhang, Xiayin; Wang, Ruixin; Wang, Ting; Zhang, Xulin; Dongye, Meimei; Wang, Dongni; Wang, Jinghui; Li, Wangting; Wu, Xiaohang; Lin, Duoru; Lin, Haotian (Frontiers in Cell and Developmental Biology, 2021)
Background: Cryptophthalmos is characterized by congenital ocular dysplasia with eyelid malformation. The pathogenicity of mutations in genes encoding components of the FRAS1/FREM protein complex is well established, but the underlying pathomechanisms of this disease are still unclear. In the previous study, we generated mice carrying Frem2R725X/R2156W compound heterozygous mutations using CRISPR/Cas9 and showed that these mice recapitulated the human cryptophthalmos phenotype. Methods: In this study, we tracked changes in the metabolic profile of embryos and expression of metabolism-related genes in Frem2 mutant mice on E13.5 compared with wild-type mice. RNA sequencing was utilized to decipher the differentiated expression of genes associated with metabolism. Untargeted metabolomics and targeted metabolomics analyses were performed to detect and verify the shifts in the composition of the embryonic metabolome. Results: Differentially expressed genes participating in amino acid metabolism and energy metabolism were observed by RNA sequencing. Transcriptomic analysis suggests that 821 (39.89%) up-regulated genes and 320 (32.99%) down-regulated genes were involved in the metabolic process in the enriched GO terms. A total of 92 significantly different metabolites were identified including creatine, guanosine 5'-monophosphate, cytosine, cytidine 5'-monophosphate, adenine, and L-serine. Interestingly, major shifts related to ATP binding cassette transporters and the biosynthesis of amino acids in the composition of the embryonic metabolome were observed by KEGG metabolic analysis, indicating that these pathways could also be involved in the pathogenesis of cryptophthalmos. Conclusions: We demonstrate that Frem2 mutant fetal mice have increased susceptibility to the disruption of eye morphogenesis in association with distinct transcriptomic and metabolomic signatures. Our findings suggest that the metabolomic signature established before birth may play a role in mediating cryptophthalmos in Frem2 mutant mice, which may have important implications for the pathogenesis of cryptophthalmos.